Bottom-Up State Building - Alda, Erik; Willman, Alys M. (World Bank, 2012)
Haiti is a showcase for the global distribution and pattern of violence that have been changing from the large-scale civil wars that prevailed until the late 1990s to the increasing emergence of common violence, particularly in urban areas.